2008
DOI: 10.1128/aac.00640-08
|View full text |Cite
|
Sign up to set email alerts
|

Tet 42, a Novel Tetracycline Resistance Determinant Isolated from Deep Terrestrial Subsurface Bacteria

Abstract: Tet 42, a novel tetracycline resistance determinant from deep subsurface bacteria, was characterized and found to have a 30% sequence similarity to TetA(Z). The protein is a putative efflux pump that shares characteristics with previously characterized pumps, including a divergently transcribed TetR repressor, a conserved GxxSDRxGRR motif, and transmembrane domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The other Group-6 member is OtrC, a predicted ABC transporter from the oxytetracycline producer Streptomyces rimosus. The determinants discovered since these classifications were examined for their similarity to other tetracycline resistance elements using the antibiotic resistance gene (39) [21], Tet(41) [22], and Tet(42) [23] showed high similarity among themselves and to Tet(C) and so can be added to Group-1, whereas Tet(40) [24] with 43.4% average similarity to TetA(P) is placed in Group-4. Tet (38) [25] is another 14 TMS protein.…”
Section: Tetracycline Effluxmentioning
confidence: 99%
“…The other Group-6 member is OtrC, a predicted ABC transporter from the oxytetracycline producer Streptomyces rimosus. The determinants discovered since these classifications were examined for their similarity to other tetracycline resistance elements using the antibiotic resistance gene (39) [21], Tet(41) [22], and Tet(42) [23] showed high similarity among themselves and to Tet(C) and so can be added to Group-1, whereas Tet(40) [24] with 43.4% average similarity to TetA(P) is placed in Group-4. Tet (38) [25] is another 14 TMS protein.…”
Section: Tetracycline Effluxmentioning
confidence: 99%
“…The majority of TCs are excreted into the environment via various pathways (e.g., agricultural runoff), and there is potential for resistance selection among pathogens and nonpathogens (8,14). To date, more than 40 classes of tetracycline resistance (tet) genes have been described in various environments (15,16), which encode three main resistance mechanisms (efflux pump proteins, ribosomal protection proteins (RPPs), and inactivating enzymes) (16). In China, tetracycline-resistant bacteria (e.g., Escherichia coli) and tet genes have been found in different water environments (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of TetR, the ␣ 8-␣ 9 loop seemed the most promising region to this end. Among the 15 different naturally occurring TetR orthologues known to date [Agersø and Guardabassi, 2005;Berens and Hillen, 2004;Brown et al, 2008;Thompson et al, 2007], little primary sequence conservation is observed within the loop, which is 12 to 21 amino acids long. This also holds true for the unique loops of the TetR variants described here.…”
Section: Discussionmentioning
confidence: 99%